2012
DOI: 10.1007/s00134-011-2460-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of pediatric index of mortality 2 (PIM2) in a single pediatric intensive care unit in Japan

Abstract: At the largest PICU center in Japan, the PIM2 was found to have excellent discriminatory power and good calibration, although it over-predicted deaths. Based on these results, PIM2 can be used as a good prediction model for pediatric mortality, which is a tool used to assess the overall quality of care in a PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 28 publications
4
29
0
2
Order By: Relevance
“…19,21 On the other hand, a Japanese study reported PIM 2 SMR <1 (0.77), which meant the score had overpredicted mortality. 23 The discrimination was evaluated by AUC. Discrimination is considered to be very good for ROC >0.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 On the other hand, a Japanese study reported PIM 2 SMR <1 (0.77), which meant the score had overpredicted mortality. 23 The discrimination was evaluated by AUC. Discrimination is considered to be very good for ROC >0.…”
Section: Discussionmentioning
confidence: 99%
“…In Argentina, Eulmesekian [35] found that the standardized mortality ratio for PIM2 was 0.85. In Japanese PICU, Imamura [36] found that the standardized mortality was 0.77. Atti [29] in Italy found that Standardized mortality ratio was 0.7.…”
Section: Results:-mentioning
confidence: 99%
“…8 It is recent, freely available while many other rating tools need a license and in addition, PIM2 has a small number of variables, thus it is easily calculated. 4,9 We aimed in the current study to assess the performance of PIM2, in terms of discriminatory ability and calibration in a sample of Egyptian children admitted to the PICU.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Mortality prediction models are useful in PICU settings as risk assessment tools and as a benchmark for the quality of care between facilities. 4 Prediction tools must discriminate well between survivors and non-survivors and be well calibrated before they can be applied usefully to assess or standardize comparisons of PICUs or to correct for case-mix differences between groups in observational studies. 5 Pediatric Index of Mortality (PIM) was first developed in 1997 6 and as most other prognostic scoring systems, was upgraded to PIM2, which was observed to have better predictability of the outcome of pediatric patients admitted to intensive care.…”
Section: Introductionmentioning
confidence: 99%